THE COURTS AND TREATIES: INDONESIA’S PERSPECTIVE - Damos Dumoli Agusman (International Law Department, Faculty of Law Universitas Padjadjaran, 2017)
AbstractThis article discusses the enforceability of treaties under Indonesian legal system. The purpose of this article is to explore and provide answers to the following questions: (i) whether or not international law may be directly invoked and enforceable under domestic legal system (ii) how and to what extent Indonesian courts are using international law especially the treaties. In providing analysis to the above questions, this article discusses the notion of courts and judicial competence and judicial attitude towards treaties. This article suggests that there is no doubt that the courts may apply treaty provisions to the case at hand without and by virtue of national legislations. However, the attitude of the courts towards treaties as demonstrated in a number of cases above does not reveal any clear indication on the question of the status of treaties under domestic law especially with regard to the method on how the legal system incorporates treaties under domestic law. The Court decision has therefore not yet contributed to the attempt for seeking a legal determination of the domestic status of a treaty as well as the mode for granting its domestic validity.Keywords: domestic validity, Indonesian perspective, monism and dualism, status of treaties and treaty practices.AbstrakArtikel ini membahas mengenai pemberlakuan perjanjian internasional dalam sistem hukum Indonesia. Tujuan dari artikel ini adalah untuk mengkaji dan memberikan jawaban atas pertanyaan-pertanyaan berikut ini: (i) apakah hukum internasional dapat secara langsung dijadikan rujukan dan berlaku dalam sistem hukum domestik (ii) bagaimana dan sampai mana pengadilan Indonesia menggunakan hukum internasional khususnya perjanjian internasional. Dalam memberikan analisis terhadap pertanyaan-pertanyaan diatas, artikel ini membahas perihal pengadilan dengan kompetensi yudisialnya, dan perilaku yudisial terhadap perjanjian internasional. Artikel ini berkesimpulan bahwa pengadilan dapat menerapkan langsung perjanjian internasional terhadap perkara. Namun demikian praktik pengadilan dalam beberapa perkara yang terkait dengan perjanjian internasional belum memberikan indikasi yang jelas tentang kedudukan hukum perjanjian. Putusan Pengadilan oleh karena itu belum berkontribusi dalam upaya untuk mencari determinasi hukum terkait status domestik dari suatu perjanjian internasional dan cara pemberlakuan suatu perjanjian internasional dalam hukum domestik.Kata kunci: monisme dan dualisme, praktek perjanjian internasional, perspektif Indonesia, status perjanjian internasional, validitas domestik.